The architectural plan and the moving image. Audio-visual media for the plan: to document, to present, to diffuse. - Gagliardi, Maria Letizia (DISEGNARECON, 2009)
The architecture needs to be communicated and to communicate, that’s why, in every period, the architect has used innovative tools which could “make public” his work. From the convention of the architectural drawing, to the prospective, photography, cinema, computer and tele-vision, architecture’s communication has found in the dynamic image the right tool for the representation of the relation between space, time and human being, a relation which implies contrasts and framings, that is a succession of images.In this article we will identify three different ways of telling architecture through moving images, three narrations that correspond to three different techniques of planning, shooting and post-production: the documentary, the simulation and the tele-vision.